In vitro antidiabetic activity of Nisamalaki Churna - Ashok Kumar, B.S.; Manjunath, N.K.; Khan, Saleemulla; Saran, Gopi Setty; Nandeesh, R. (Universiti Kebangsaan Malaysia, 2013)
Nisamalaki Churna is an Ayurveda formulation used for diabetes, which consists of amalaki and haridra. In vitro antidiabetic screening of Nisamalaki Churna by α-amylase inhibition was carried out by starch iodine method, initrosalicylic acid method (DNSA) and effect on normal rats blood sugar level was studied. Nisamalaki Churna shows potent α-amylase inhibition IC50 89.44 μg/mL by starch iodine method and IC50100.0 μg/mL by DNS method. Nisamalaki Churna showed potent decrease in blood glucose level in normal rats.